Juridical Study of Application of Land Based Grants for Children under Age (Minors) In Purwokerto City - Kusdyastuti Pratiwi; Boma Wira Gumilar; Akhmad Khisni (Jurnal Akta, 2019)
The purpose of this study was to identify and analyze: 1) Implementation of Land Rights Application Based Grants for Children Under Age in Purwokerto. 2) Barriers to Land Rights Application Process. 3) solution or an attempt to overcome barriers that arise in the Land Rights Application Process Based Grants for Children Under Age in Purwokerto.The approach method in this research is juridical empirical research that emphasizes the behavior of individuals or communities in connection with the law. The data used are primary and secondary data obtained through interviews and literature, while the method of data analysis was done with descriptive and qualitative analysis.Results of the research can be concluded: 1) Implementation of Land Rights Application Based Grants for Children Under Age in Purwokerto are filing a trust, do grant agreement, made a grant deed in front of PPAT. To get the grant deed, PPAT Purwokerto provide the terms of a document that must be completed. Furthermore PPAT within a period of seven (7) days after the grant deed signed certificates are required to submit the following relevant documents to the Land Office to be registered switchover rights. 2) Barriers experienced from the Land Deed Official (PPAT) is data required SVTO not exist, it can happen PPAT delay the process to wait until the publication of SPPT of the UN office. In the Land Office, Officers from the land office convoluted in keterangannnya. The resistance of the people or the Applicant is the difficulty in the process of application for registration which is due to a lack of public knowledge about the registration of land. 3) The solution or an attempt to overcome barriers that are PPAT could short SVTO asked for a letter to the UN office, to the Land Office can provide public education related to easy and the importance of land registration. For the public to be more active in seeking information about the application process transition of land rights.Keywords: Grant; Children under Age; Certificate of Land.